Respuesta :
Answer:
First one:
4 x minus 5 y = negative 5 and 3 x + 10 y = negative 20
Step-by-step explanation:
4 x - 5 y = -5 (1)
3 x + 10 y = -20 (2)
Multiply (1) by 2 and add to (×)
8x - 10y = -10
3x + 10y = -20
11x = -30
x = -30/11 = -2.727272
x = -2.7
4(-30/11) - 5y = -5
5y = -65/11
y = -13/11 = -1.18181818
y = -1.2
Answer:
4 x - 5 y = - 5 and 3 x + 10 y = - 20
Step-by-step explanation:
4 x - 5 y = -5 (1)
3 x + 10 y = -20 (2)
Multiply (1) by 2 and add to (×)
8x - 10y = -10
3x + 10y = -20
11x = -30
x = -30/11 = -2.727272
x = -2.7
4(-30/11) - 5y = -5
5y = -65/11
y = -13/11 = -1.18181818
y = -1.2
hope this helps..